ANALISIS PENINGKATAN PRODUKSI DENGAN RANCANG BANGUN ALAT PEMOTONG PADA PROSES PACKING: rancangan bangun alat pemotong dalam peningkatan produksi - Ganda Sirait; Elva Susanti (Universitas Putera Batam, 2020)
Improving company productivity and efficiency in empowering human resource assessment is fulfilled to achieve company goals. one factor that can be done is the development of more effective equipment. Plastic cutting tools in the product packaging process are still simple, less efficient and less effective. The value engineering method is used as a method for selecting an alternative modification to a modified cutting tool and analyze it. At the analysis stage, two alternative modifications were modified from the improvement engine, where the initial design is used as a benchmark in performance evaluation. The result of tool design is the reduction in the number of defective products by 20.68% to 3.1% and The result of the cutting tool design is that there is an average increase in production 246 products per day.